Scalable salt-templated synthesis of two-dimensional transition metal oxides - Xiao, Xu; Song, Huaibing; Lin, Shizhe; Zhou, Ying; Zhan, Xiaojun; Hu, Zhimi; Zhang, Qi; Sun, Jiyu; Yang, Bo; Li, Tianqi; Jiao, Liying; Zhou, Jun; et al. (Nature communications, 2016)
Two-dimensional atomic crystals, such as two-dimensional oxides, have attracted much attention in energy storage because nearly all of the atoms can be exposed to the electrolyte and involved in redox reactions. However, current strategies are largely limited to intrinsically layered compounds. Here we report a general strategy that uses the surfaces of water-soluble salt crystals as growth templates and is applicable to not only layered compounds but also various transition metal oxides, such as hexagonal-MoO 3 , MoO 2 , MnO and hexagonal-WO 3 . The planar growth is hypothesized to occur via a match between the crystal lattices of the salt and the growing oxide. Restacked two-dimensional hexagonal-MoO 3 exhibits high pseudocapacitive performances (for example, 300 F cm −3 in an Al 2 (SO 4 ) 3 electrolyte). The synthesis of various two-dimensional transition metal oxides and the demonstration of high capacitance are expected to enable fundamental studies of dimensionality effects on their properties and facilitate their use in energy storage and other applications. Two-dimensional atomic crystals are known to be effective electrode materials for energy storage applications. Here, the authors report the preparation of various two-dimensional metal oxides, including those which do not have a layered parent structure, via a salt templating strategy.